Borderland on fire. Fires in Raczki in 1811–1911 - Halicki, Marcin Sebastian (Marginesy, 2021)
The article Borderline on fire. Fires in Raczki in 1811–1911 [„Pogranicze w ogniu. Pożary Raczek w latach 1811–1911”] oscillates around fires and firefighting in the former town and subsequently in the town settlement of Raczki – a place located, until 1945, in the vicinity of the Polish‑Prussian borderland in the Suwałki region. The key to developing the article was the recreation and comparison of journalistic messages undertaken by both the national and regional press. The factual grounds of the text were outlined on the basis of information about the town contained in the 19th century archival documentation. Whereas the aim of the topic was to undertake and analyse information presented primarily in periodicals from the epoch. The text presents the largest fires in the town and makes a brief analysis of probable causes. The analysis of the archival materials showed several significant events that took place between 1811 and 1911. The article uses iconographic materials to illustrate the image of the settlement of that time more comprehensively.